Individual carbon and oxygen isotopes measurements from heterogeneous basement samples from the Atlantis Massif, IODP Expedition 357 - Lotta Ternieten; Gretchen L Früh-Green; Stefano M Bernasconi (PANGAEA, 2021)
The carbon geochemistry of serpentinized peridotites, gabbroic rocks, and sediments recovered during IODP Expedition 357 (October to December 2015) on the Atlantis Massif, Mid-Atlantic Ridge was examined to characterize carbon sources and the fate of dissolved organic (DOC) and inorganic carbon (DIC) in seawater during long-lived hydrothermal circulation and serpentinization. The measurements were performed at the ETH Zurich, Geological Institute from 2017 to 2020 using a GasBench II connected to a Delta V Mass Spectrometer.